Sobre la nomenclatura de una especie del género Asteriscus Mill. (Asteraceae). - Blanca, Gabriel; Cueto, Miguel (Acta Botanica Malacitana, 2007)
On the nomenclature of a species of the genus Asteriscus Mill. (Asteraceae) Palabras clave. Asteriscus, nomenclatura, Península Ibérica, N África. Key words. Asteriscus, nomenclature, Iberian Peninsula, N Afrique.